Gender differences in competitiveness - Mario Lackner (IZA World of Labor, 2016)
Differences in labor market outcomes for women and men are highly persistent. Apart from discrimination, one frequently mentioned explanation could be differences in the attitude towards competition for both genders. Abundant empirical evidence indicates that multiple influences shape attitudes towards competition during different periods of the life cycle. Gender differences in competitiveness will not only influence outcomes during working age, but also during early childhood education. In order to reduce the gender gap in educational and labor market outcomes, it is crucial to understand when and why gender gaps in competitiveness arise and to study their consequences.
Keywords: J20; J30; 330; gender; competitiveness; labor markets; education